Analysis of Differences in pH and Unstimulated Salivary Flow Rate in Students Consuming Green Tea Once and Three Times Daily for Seven Days at YARSI University and Its Review from an Islamic Perspective - Silvia Zalia; Audiawati Surachmin; Sonya Priyadharsini; Siti Nur Riani (Lembaga Penelitian Universitas YARSI, 2026)
Background: Saliva is a crucial biological fluid in maintaining oral homeostasis through its buffering capacity and mechanical cleansing functions. Green tea (Camellia sinensis) contains bioactive polyphenolic compounds, particularly catechins, which have the potential to modulate the chemical environment of saliva. Objective: This study aimed to analyze the differences in salivary pH and unstimulated salivary flow rate among individuals consuming green tea once daily compared to three times daily for seven days. Methods: This quasi-experimental study involved 30 participants divided into Group A (once daily), Group B (three times daily), and a control group. Saliva samples were collected using the spitting method. Data were analyzed using the GLM Repeated Measures test and the Friedman test. Results: A significant increase in salivary pH was observed in all groups (p-value < 0.05), with the highest stability found in the group consuming green tea three times daily. However, no significant changes were observed in unstimulated salivary flow rate across all groups (p-value ≥ 0.05). Conclusion: Green tea consumption significantly improves salivary quality (pH) without affecting the quantity of secretion (flow rate). This practice aligns with the principles of maqāṣid al-sharī‘ah, particularly ḥifẓ al-nafs (preservation of life/health), as a form of human responsibility in maintaining physical well-being as a trust from Allah SWT.